The capture of injected 1+ ions in charge breeder electron cyclotron resonance ion source plasma. (1st December 2022) - Tarvainen, O; Angot, J; Thuillier, T; Migliore, M; Maunoury, L; Chauveau, P
Abstract: The capture process of the 1+ ions in charge breeder electron cyclotron resonance ion sources has been attributed to cumulative small-angle scattering of the incident ions in ion–ion collisions with the buffer gas ions. The model results in controversy between the plasma potential and ion temperature values derived from simulations, and those found in the experiments. We demonstrate that the 1+ ion capture process is dominated by the slowing down of the incident ions by the ambipolar plasma potential, which has previously been assigned with a secondary importance. In this revised view, supported by experimental data, the 1+ capture does not depend on the mass of the injected and plasma ion species, or the ion temperature, which resolves the disagreement between modelling and experiments.